T cell immunity to Zika virus targets immunodominant epitopes that show cross-reactivity with other Flaviviruses - Reynolds,CJ; Suleyman,OM; Ortega-Prieto,AM; Skelton,JK; Bonnesoeur,P; Blohm,A; Carregaro,V; Silva,JS; James,EA; Maillere,B; Dorner,M; Boyton,RJ; et al. (Scientific Reports, 2018)
Zika virus (ZIKV) Infection has several outcomes from asymptomatic exposure to rash, conjunctivitis, Guillain-Barré syndrome or congenital Zika syndrome. Analysis of ZIKV immunity is confounded by the fact that several related Flaviviruses infect humans, including Dengue virus 1–4, West Nile virus and Yellow Fever virus. HLA class II restricted T cell cross-reactivity between ZIKV and other Flaviviruses infection(s) or vaccination may contribute to protection or to enhanced immunopathology. We mapped immunodominant, HLA class II restricted, CD4 epitopes from ZIKV Envelope (Env), and Non-structural (NS) NS1, NS3 and NS5 antigens in HLA class II transgenic mice. In several cases, ZIKV primed CD4 cells responded to homologous sequences from other viruses, including DENV1–4, WNV or YFV. However, cross-reactive responses could confer immune deviation - the response to the Env DENV4 p1 epitope in HLA-DR1 resulted in IL-17A immunity, often associated with exacerbated immunopathogenesis. This conservation of recognition across Flaviviruses, may encompass protective and/or pathogenic components and poses challenges to characterization of ZIKV protective immunity.